1998
DOI: 10.1017/s0950268898008917
|View full text |Cite
|
Sign up to set email alerts
|

Absence of relationship between Schistosoma japonicum and hepatitis B virus infection in the Dongting lake region, China

Abstract: In order to determine whether infection with Schistosoma japonicum is related to a higher rate of infection with hepatitis B virus and/or to a higher probability of HBsAg chronic carriage, a population based survey was carried out in China in which HBV markers were studied in 112 subjects with long-lasting S. japonicum infection, and 93 subjects with no S. japonicum infection 37.5% of the cases and 40.9% of controls showed no markers of HBV infection. The prevalence rate of HBsAg was 12.5% in the cases and 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This observation could be explained by an increased susceptibility to HBV caused by schistosome infections. On the other hand, there are reports of no relationship between schistosomiasis and HBV [ 86 , 87 ]. In addition, experiments with animals do not support increased susceptibility to HBV in schistosomiasis.…”
Section: Effects Of Schistosomes On Immunological Disorders or Infmentioning
confidence: 99%
“…This observation could be explained by an increased susceptibility to HBV caused by schistosome infections. On the other hand, there are reports of no relationship between schistosomiasis and HBV [ 86 , 87 ]. In addition, experiments with animals do not support increased susceptibility to HBV in schistosomiasis.…”
Section: Effects Of Schistosomes On Immunological Disorders or Infmentioning
confidence: 99%
“…Very few (and contradictory) studies describing possible interactions between HBV and S. mansoni are available. Although some studies have shown little or no epidemiological association between S. mansoni infection and the presence of antibody to hepatitis B virus core antigen (anti-HBc) and hepatitis B surface antigen (HBsAg) (16)(17)(18)(19), others have shown that concurrence of these two infections correlates with a more severe liver disease and a longer persistence of HBsAg (20,21). Based on the results of this report, it is possible that Th1-type cytokines may inhibit HBV replication during human S. mansoni infection, irrespective of the presence of Th2-type cytokines in the liver.…”
Section: Inhibition Of Hbv Replication During S Mansoni Infectionmentioning
confidence: 99%
“…However, this could be explained by the frequent need of schistosomiasis patients for blood transfusion, especially on considering the poor infection control measures in countries where this disease is endemic. In contrast, other studies rejected the thesis stating any relationship between schistosomiasis and HBV [ 48 , 49 ]. Woodchucks are susceptible to infection with both schistosoma and woodchuck hepatitis virus (WHV) [ 50 ].…”
Section: Introductionmentioning
confidence: 99%